ITKAS spearheads Bera District Branding Research - Mohd Zaki, Ahmad (2021)
BANGI, 14 October 2021 - The Institute of Civilisation and Strategic Studies (ITKAS), Universiti Malaysia Pahang (UMP), in collaboration with the Pahang State Government, will lead the Bera District Branding Research through a consultancy project under the supervision of UMP Holdings Sdn. Bhd. starting at the end of this month.